ANALISIS BELANJA DAERAH PEMERINTAH KOTA MAGELANG TAHUN 2015-2019 - Endah Purwaningsih; Priyono, Nuwun (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2021)
Local Expenditure is all local government obligations recognized as a reduction in the value of net worth within the period of the relevant fiscal year. The government's success in managing regional spending can be seen from the output/results achieved by using the budget. Whether the achievement of the results provides benefits to the community or not. Good results show that local governments are performing well. The purpose of this research is to find out the financial performance of Magelang city government by conducting analysis of regional spending in fiscal year 2015-2019. The method used in this study is quantitative data measurement which results are interpreted with descriptive analysis methods. The results of this study show the Magelang City Government has been performing quite well. This is seen from the variance analysis showing budget planning and efforts to achieve budget usage efficiency are good enough, spending growth is volatile and positive, and the cost efficiency ratio is quite effective with an average efficiency rate of 85.47%. Even so, the Government still needs to improve the balance between capital expenditure and operating expenditure.